2018
DOI: 10.1007/s40843-018-9342-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid microwave-assisted refluxing synthesis of hierarchical mulberry-shaped Na3V2(PO4)2O2F@C as high performance cathode for sodium & lithium-ion batteries

Abstract: Unique hierarchical mulberry-shaped Na 3 V 2 (PO 4 ) 2 O 2 F@C nanocomposite was fabricated by a rapid microwave-assisted low-temperature refluxing strategy. The V(acac) 3 reverse micelle systems in the water-in-oil microemulsions played key roles in forming the self-assembly architectures. The prepared Na 3 V 2 (PO 4 ) 2 O 2 F@C nanoparticles with the anisotropic growth along the [002] direction were in-situ encapsulated in carbon shells, which greatly contribute to fast Na + /e − transfer in electrodes. And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…For instance, dealing with this last approach, it was shown that nanosizing carbon coated‐NVPF by mechanical activation improves high rate capacity and cycling stability [22] . Although it is well known that particle's size and morphology influence the energy storage performance and a lot of particle shapes can be obtained, such as nano or microspheres, [23–25] hollow spheres, [19,26,27] nano or microcubes, [28–30] nano‐flowers, [31,32] platelets [33] and other special morphologies, [34–40] it is still unclear which particle's morphology allows to reach the best high‐rate performance and if the synthesis method influences the electrochemical properties. Indeed, different electrode formulations, nature of electrolytes, active mass loadings, carbon coatings or conductive additives make very complicated a simple comparison between all the studies reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, dealing with this last approach, it was shown that nanosizing carbon coated‐NVPF by mechanical activation improves high rate capacity and cycling stability [22] . Although it is well known that particle's size and morphology influence the energy storage performance and a lot of particle shapes can be obtained, such as nano or microspheres, [23–25] hollow spheres, [19,26,27] nano or microcubes, [28–30] nano‐flowers, [31,32] platelets [33] and other special morphologies, [34–40] it is still unclear which particle's morphology allows to reach the best high‐rate performance and if the synthesis method influences the electrochemical properties. Indeed, different electrode formulations, nature of electrolytes, active mass loadings, carbon coatings or conductive additives make very complicated a simple comparison between all the studies reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also put tremendous effort into further improving the electrochemical performance of this oxyfluorophosphate material by various strategies, such as transition metal element doping, carbon matrix designs unique morphologies control, etc. [ 185–195 ] Very recently, Ceder's group tried to utilize the V 4+ /V 5+ redox couple by inserting additional sodium into the vanadium oxyfluorophosphate solid solution Na 3 V 2 (PO 4 ) 2 F 3‐ y O 2 y (0 ≤ y ≤ 1). [ 176 ] Na 4 V 2 (PO 4 ) 2 FO 2 was observed upon discharging at ≈1.6 V with extended capacity up to 165 mAh g −1 (Figure 14h).…”
Section: Alkali‐ion Containing Composites For Sodium and Potassium Stmentioning
confidence: 99%
“…[ 180 ] Full cell with hard carbon anode delivered a specific capacity of 120 mAh g −1 at a working voltage of 3.1 V. [ 181 ] Recently carbon encapsulated N3VOPF was synthesized by rapid microwave‐assisted technique and delivered a capacity of 127.9 mAh g −1 with 82.1% retention after 2000 cycles at 20 C rate. [ 182 ] It also led to good rate kinetics and cycling performances of N3VOPF in lithium half‐cell configuration. Zhang et al.…”
Section: Fluorophosphatesmentioning
confidence: 99%